2020
DOI: 10.4111/icu.2020.61.4.390
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of neoadjuvant chemotherapy use in muscle-invasive bladder cancer

Abstract: Cisplatin-based neoadjuvant chemotherapy (NAC) followed by radical cystectomy (RC) is standard of care for muscleinvasive bladder cancer (MIBC). However, NAC is used in less than 20% of patients with MIBC. Our goal is to investigate factors that contribute to underutilization NAC to facilitate more routine incorporation into clinical practice. Materials and Methods: We identified 5,915 patients diagnosed with cT2-T3N0M0 MIBC who underwent RC between 2004 and 2014 from the National Cancer Database. Univariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Our results are consistent with and extend upon these findings by demonstrating travel distance and United States geographic region to be additional independent determinants of NAC use in these patients. While other recent studies have explored geographic determinants of chemotherapy for MIBC, those identified in our literature search must be interpreted in view of the fact that they did not specify tumour histology, 9 included both urothelial and non‐urothelial histology 10 or considered all forms of perioperative chemotherapy (ie, NAC or adjuvant chemotherapy) together 11 . Thus, to our knowledge, our study was the first to model determinants of NAC in patients undergoing RC for cT2‐cT4a/N0M0 urothelial MIBC while incorporating factors related to transportation and geography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with and extend upon these findings by demonstrating travel distance and United States geographic region to be additional independent determinants of NAC use in these patients. While other recent studies have explored geographic determinants of chemotherapy for MIBC, those identified in our literature search must be interpreted in view of the fact that they did not specify tumour histology, 9 included both urothelial and non‐urothelial histology 10 or considered all forms of perioperative chemotherapy (ie, NAC or adjuvant chemotherapy) together 11 . Thus, to our knowledge, our study was the first to model determinants of NAC in patients undergoing RC for cT2‐cT4a/N0M0 urothelial MIBC while incorporating factors related to transportation and geography.…”
Section: Discussionmentioning
confidence: 99%
“…Access to transportation and related resources merits greater consideration in the context of social determinants of health in bladder cancer care. must be interpreted in view of the fact that they did not specify tumour histology, 9 included both urothelial and non-urothelial histology 10 or considered all forms of perioperative chemotherapy (ie, NAC or adjuvant chemotherapy) together. 11 Thus, to our knowledge, our study was the first to model determinants of NAC in patients undergoing RC for cT2-cT4a/N0M0 urothelial MIBC while incorporating factors related to transportation and geography.…”
Section: What's Newmentioning
confidence: 99%
“…Retrospective studies have clearly shown that C-NAC is underutilized worldwide, although recent surveys indicate an increase in its application since 2010 [12,13]. The potential clinical reasons contributing to the underutilization of C-NAC in elderly patients include older age as well as higher comorbidity scores [6][7][8]. Based on a national database from the United States and Porto-Rico, Carvalho et al reported that only 18.8% of patients aged ≥ 75 received C-NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 81.2% of patients who did not receive C-NAC, only 2.5% were ineligible due to true contraindication. In addition, 68% of patients did not receive C-NAC simply because it was not planned, implying that this treatment option may not even be offered or discussed by some providers after the initial diagnosis of MIBC [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation